2014
DOI: 10.4018/ijismd.2014040101
|View full text |Cite
|
Sign up to set email alerts
|

Service Innovation Analytics

Abstract: The importance of innovation for firms for gaining competitive advantage has been widely acknowledged. Innovation in services exhibits some particular challenges. In order to support formal service innovation management, several frameworks of capabilities for service innovation have been published in recent years. However, these frameworks often do not support the use of existing information to apply them to a firm's context and to guide managerial decisions. In this paper the authors aim to show that a firm's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Generally, AI advancements can achieve performance enhancement as a result of speed, flexibility, customization, scale, innovation, and decision-making [11,26]. Moreover, organizations have many benefits from the utilization of AI to create value across various organizational components: process automation; obtaining knowledge from data for decision-making; involving consumers and employees; developing and launching new products and services [7,12,[57][58][59][60][61].…”
Section: Artificial Intelligence and Machine Learning In Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, AI advancements can achieve performance enhancement as a result of speed, flexibility, customization, scale, innovation, and decision-making [11,26]. Moreover, organizations have many benefits from the utilization of AI to create value across various organizational components: process automation; obtaining knowledge from data for decision-making; involving consumers and employees; developing and launching new products and services [7,12,[57][58][59][60][61].…”
Section: Artificial Intelligence and Machine Learning In Organizationsmentioning
confidence: 99%
“…Ref. [60] suggested that AI is rapidly reconstructing the service, executing different functions, becoming a significant source of innovation and generating opportunities for innovative human-machine interaction.…”
Section: Ai Service Innovation and Valuementioning
confidence: 99%
“…Apart from the motives and impediments that a firm perceives from MS, it is essentials to know which environmental and internal factors can affect the development of organizational innovative activities (Kohler et al, 2014). Tornatzky and Fleisher's (1990) Technology-Organization-Environment (TOE) framework addresses three key facets related to the firms that adopt a given technology: the technological context, the organizational context and the environmental context.…”
Section: Do Toe Variables Affect the Adoption Of Mobile Selling?mentioning
confidence: 99%
“…Durante mucho tiempo, los trabajos de investigación en el sector servicios eran incipientes, y en general, el sector era poco estudiado (Fundación COTEC, 2001;ISEA, 2008;Romero & López, 2015;Cardona, Balza & Henríquez, 2017). Pero recientemente comenzó a recibir una atención significativa de investigadores y formuladores de políticas, al reconocer que los servicios pueden ser dinámicos (Jacob, Tintoré & Torres, 2001;Kohler, Feldmann, Habryn & Satzger, 2013;Robayo, 2017).…”
Section: Introductionunclassified